MotoGP Mandalika 2022 Sentiment Classification Using Machine Learning - Pardede, Doughlas; Hayadi, B. Herawan (Jurnal Transformatika, 2023)
MotoGP is a world-class motorcycle racing event, which will be held in the 19th series in 2022 at the Pertamina Mandalika Circuit. This study tries to analyze public sentiment collected from the results of tweeter social media tweets, in the form of sentiment and emotion values. With the features of sentiment and emotion values extracted from the contents of this tweet, k-means clustering is used to generate sentiment clusters as targets for classification using the MLP algorithm. From the results of the evaluation using 10-fold cross validation, the accuracy value is 97%, the precision value is 94.64% and the recall value is 100%. The classification results also show that the public response to the 2022 MotoGP event at the Mandalika circuit is quite balanced, where 53% have a positive response, while the rest have a negative response